THE WAY WEBTOON MAINTAINS JAVANESE LANGUAGE: AN ANALYSIS OF JAMU GENDONG MBOK DE COMIC - Farahsani, Yashinta; Rini, Ika Puspita; Jaya, Patria Handung (HUMANIKA, 2018)
In this sophisticated era, teenagers tend to close to technology for their communication. One of the communication technology they use is LINE. Beside for communication, LINE also has several services for entertainment, and one of them is webtoon. Webtoon provides online comics to be enjoyed by everyone. Webtoon is an application from Korea which spreads around the world and each country can create domestic comics to be published in webtoon. In Indonesia, webtoon is more and more popular, especially for young generation. It published many comics, either in Indonesian language or mixed with regional languages. Some comics are created in mixed Indonesian and Javanese language, for example Jamu Mbok De. The use of Javanese in that comic helps a lot in the Javanese maintenance. By reading that comic, the Javanese young generation becomes more familiar with Javanese. In which nowadays, they prefer to use Indonesian rather than Javanese because of the environment. Therefore, there are less and less effort to maintain the Javanese language which impacts to Javanese daily usage. By publishing comics in Webtoon using mixed Indonesian and Javanese, it can be one of the way to maintain the regional language.